Vaginal discharge syndrome (vaginitis / vaginosis): Diagnostic and therapeutic update: Vaginal discharge syndrome (vaginitis / vaginosis): diagnostic and therapeutic update - Espitia, Franklin De La Hoz (2021)
Objective: to update the diagnosis and therapy in vaginal discharge syndrome (vaginitis / vaginosis), in pregnant and non-pregnant women. Materials and methods: a systematic review and bibliographic search of the literature in different electronic databases was carried out to identify relevant literature: Embase, Medline, Pubmed, among others, and printed textbooks; by means of free and standardized search terms. Between January 1991 and January 2021; no language restriction. Comparators included bacterial vaginosis (BV), vulvovaginal candidiasis (CVV), and Trichomonas vaginalis infection.  Results: 93 studies were included. BV is the most prevalent vaginal infection (40-50%) in women of reproductive age, followed by CVV (20-25%). Candida albicans is the most prevalent species (60.3%); while of the non-albicans Candida species, Candida tropicalis (9.9%) and Candida glabrata (12.2%) are the most prevalent. Gardnerella vaginalis is the cause of 19.5% of BV. Vaginal trichomoniasis is the most common Sexually Transmitted (Non-Viral) Infection (0.8-3.2%). Conclusions: BV is the most prevalent vaginal infection in women of reproductive age, followed by CVV. Candida albicans is the most prevalent species in CVV while Gardnerella vaginalis predominates in BV. Urgent intervention actions are required to improve vaginal infection prevention measures, in order to reduce both the prevalence and complications.